Implication of Rational Religious Flows in Islamic Education - Muksin, Muksin (Universitas Al-Amien Prenduan, 2024)
Ibnu Miskawaih, as one of the leaders of Islamic education, emphasized that knowledge is a treasure that cannot be stolen; enlighten others and see it flourish. At the time of heyday of Islam Islamic education developed rapidly. However, nowadays as seen in modern times, faces the challenge of developing education that is relevant and able to answer the challenges of the times. One of the proposed solutions is to develop Islamic education based on rational religious beliefs, which emphasizes the importance of reason and rationality in understanding Islamic teachings. This stream makes a significant contribution to learning methods, curriculum and educational quality. This article presents the problem formulation as follows: What is the concept of Islamic education from Ibn Miskawaih's rational religious perspective? What is the relevance of rational religious beliefs for the development of Islamic education? What are the implications of rational religious beliefs for Islamic education? In writing this article, the research method chosen by the author is a qualitative research method, using a library research approach. Researchers collect data from various literary sources, such as books, articles, proceedings and journals that are related to the study that the author is reviewing.